The rocky shore invertebrates from Lima Department, Peru: a commented list of species - Paredes, Carlos (1999)
The faunistic diversity of the rocky intertidal zone of the Department of Lima, Perú, was studied in sixteen localities with emphasis in the relative dominance of the species and its vertical distribution. 175 species of invertebrates are registered, predominating the mollusks (79 species), crustaceans (44 species) and polychaete (30 species), the three taxa that predominate in the benthos marine. Considering the communities studied 41% for Perumytilus purpuratus are registered, 34% in Semimytilus algosus and 50% of the species for Phragmatopoma moerchi. Diversity and zonation are generalized for the Peruvian Province.